Identification of inhibitors of the Schistosoma mansoni VKR2 kinase domain - Mathavan,I; Liu,LJ; Robinson,SW; El-Sakkary,N; Elastico,AJJ; Gomez,D; Nellas,R; Owens,RJ; Zuercher,W; Navratilova,I; Caffrey,CR; Beis,K (ACS Medicinal Chemistry Letters, 2022)
Schistosomiasis is a neglected tropical disease caused by parasitic flatworms. Current treatment relies on just one partially effective drug, praziquantel (PZQ). Schistosoma mansoni Venus Kinase Receptors 1 and 2 (SmVKR1 and SmVKR2) are important for parasite growth and egg production, and are potential targets for combating schistosomiasis. VKRs consist of an extracellular Venus Flytrap Module (VFTM) linked via a transmembrane helix to a kinase domain. Here, we initiated a drug discovery effort to inhibit the activity of the SmVKR2 kinase domain (SmVKR2KD) by screening the GSK published kinase inhibitor set 2 (PKIS2). We identified several inhibitors, of which four were able to inhibit its enzymatic activity and induced phenotypic changes in ex vivoS. mansoni. Our crystal structure of the SmVKR2KD displays an active-like state that sheds light on the activation process of VKRs. Our data provide a basis for the further exploration of SmVKR2 as a possible drug target.